Digital surveillance technologies. Ethical, anthropological and political issues - Maria Giorgia Caraceni (European Journal of Privacy Law & Technologies, 2022)
The article aims to show how, over the decades, the noble ideals underlying the technological revolution began in the last century have been betrayed. The peculiar characteristics of that system defined as ʿsurveillance capitalismʾ by Shoshana Zuboff are first described, and then the historical and cultural framework allowing it to establish itself is reconstructed. Next, the consequences on human beings, such as the lack of privacy and the restriction of fundamental rights and liberties, are analyzed and discussed. Finally, the phenomenon of mass surveillance conducted through digital tools is addressed from a political and juridical point of view. In this regard, the risks that this represents for democratic political systems and the consequent legislative response that the European Union is trying to give are debated. Finally, conclusions are drawn.